The Offline Nature of Online Community: Exploring Distance Learners’ Extracurricular Interactions - Berry, Sharla (International Review of Research in Open and Distributed Learning, 2019)
Despite the importance of interpersonal contact to students’ sense of community, little is known about how online students form relationships outside of class. Drawing on interviews with 20 students from one online doctoral program, I explore the ways in which distance learners create community outside of class. In the case study I explore how students use social media and group texting apps to develop relationships with peers. I also explore how online students connect in-person at study groups and sporting events. Lastly, I consider the ways in which a three-day, in-person orientation helped online students connect on and offline. Findings indicate that online students’ perceptions of community were not limited to their in-class experiences. In addition to their in-class interactions, online students were impacted by their extracurricular interactions in digital and physical spaces.